High Performance Thin Layer Chromatographic Standardization and Quantification of Marker Compounds in an Ayurvedic Polyherbal Formulation Padmakadi Churna - Meshram, Ravichand; Sahu, Umakant; Parihar, Arun K S; Gupta, Prashant K; Chauhan, Nagendra Singh (Indian Journal of Natural Products, 2022)
The aim of this study was to find out a simple, accurate and sensitive HPTLC method for the detection and quantification of marker molecule Gallic and Piperine in Padmakadi churna for standardization. Ethanolic extraction was performed for analysis. HPTLC was done using gallic acid and Piperine as a standard. The mobile phase was a mixture of Toulene:ethyl acetate:Ethanol:Formic acid (6:3:1:0.3 v/v/v) and detection at 254 nm. The Rf was detected at - 0.39 for Gallic acid and Rf - 0.55 for Piperine was identified in Padmakadi Churna. The simple and sensitive HPTLC method was successfully developed for determination of Gallic acid and Piperine in Padmakadi Churna. The proposed HPTLC method was found to be simple, fast and inexpensive, and can be used for the routine quality control of raw materials.
Keywords: Padmakadi Churna; Physiochemical; HPTLC; Gallic acid; Piperine; Standardization